Below the parapet wall Beautifully carved miniatures of temple tower-like structures; Carving on the parapet wall - sequences from the epic Ramayana - Rama wins against Ravana and reunites with Seeta. - Brig. Ajai Singh (2021)
[ Image courtesy: Brig A.P. Singh - www.collectingmoments.in ]